Shotgun metagenomics detects the human pegivirus complete genome in a pediatric patient with acute hepatitis of unknown etiology: a case report - Vazzana, Roberta; Mularoni, Alessandra; Vaiana, Claudia; Cona, Andrea; Mulè, Giovanni; Amato, Caterina; Ranucci, Giusy; Conaldi, Pier Giulio; Agnese, Valentina; Cuscino, Nicola; Gallo, Alessia (Frontiers in Genetics, 2025)
Human pegivirus (HPgV) is a positive-sense, single-strand RNA virus belonging to the Flaviviridae family. Although not conclusively linked to a specific disease, an increasing number of studies have recently reported an association between this virus and different human pathologies. In this study, we present a 6-month-old female infant admitted to the hospital for severe acute hepatitis. Her clinical history started with a one week of fever and diarrhea treated with paracetamol and amoxicillin–clavulanate for a total of 4 days. The persistence of the symptoms, high levels of transaminases, coagulopathy, increased lymphocytosis, and C-reactive protein (CRP) in the blood suggested an acute hepatitis episode. Serological and molecular biology tests for hepatotropic and non-hepatotropic viruses, including hepatitis B virus (HBV), hepatitis A virus (HAV), hepatitis C virus (HCV), hepatitis E virus (HEV), Epstein–Barr virus (EBV), cytomegalovirus (CMV), herpes simplex virus (HSV), enterovirus, and adenovirus, were negative. Metabolic and genetic alterations, deficiency of alpha-1 antitrypsin, and Wilson’s disease were ruled out following negative results. The child was thus treated with supportive therapy. Metagenomic next-generation sequencing (mNGS) performed to identify other possible infective agents undetected with the classical tests, showed the presence of the complete genome of human HPgV-1. This case provides further evidence supporting the hypothesis of the pathogenic role of HPgV-1 and warrants particular attention, especially in the pediatric population. Moreover, here we confirmed the diagnostic power of metagenomic-NGS in the detection of unusual pathogens.